ELECTRONIC MEDICAL RECORD (EMR) DESIGN FOR HOSPITAL USING BLOCKCHAIN TECHNOLOGY - Lee, Eugenius Hansel; Wang, Gunawan (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Data leakage in indonesia is still regarded as being extremely common, which has led to a low level of confidence among indonesians when it comes to storing their personal data online. The use of blockchain is still not popular in Indonesia.These two technologies may be merged to produce the best technical outcomes, especially in the security area, thanks to technological advancements in the healthcare industry and blockchain technology. The implementation of the EMR blockchain is also capable of facilitating the reach of the patient's medical record history, allowing each patient who receives outpatient or other treatment at one of the XYZ hospitals to easily integrate their medical records when seeking treatment at other branches, even if XYZ hospital just recently acquired another hospital. Data transmission with the standard system is still in doubt since there is no guarantee of the security of the data because the security of the new branch hospital and the acquired hospital cannot be guaranteed securely. The EMR blockchain can help all hospitals in the future by easing their concerns and facilitating hospital system mobilization, particularly in the patient data department.